Hyaluronic-Acid Based Hydrogels for 3-Dimensional Culture of Patient-Derived Glioblastoma Cells - Xiao, Weikun (J Vis Exp, 2018)
Glioblastoma (GBM) is the most common, yet most lethal, central nervous system cancer. In recent years, many studies have focused on how the extracellular matrix (ECM) of the unique brain environment, such as hyaluronic acid (HA), facilitates GBM progression and invasion. However, most in vitro culture models include GBM cells outside of the context of an ECM. Murine xenografts of GBM cells are used commonly as well. However, in vivo models make it difficult to isolate the contributions of individual features of the complex tumor microenvironment to tumor behavior. Here, we describe an HA hydrogel-based, three-dimensional (3D) culture platform that allows researchers to independently alter HA concentration and stiffness. High molecular weight HA and polyethylene glycol (PEG) comprise hydrogels, which are crosslinked via Michael-type addition in the presence of live cells. 3D hydrogel cultures of patient-derived GBM cells exhibit viability and proliferation rates as good as, or better than, when cultured as standard gliomaspheres. The hydrogel system also enables incorporation of ECM-mimetic peptides to isolate effects of specific cell-ECM interactions. Hydrogels are optically transparent so that live cells can be imaged in 3D culture. Finally, HA hydrogel cultures are compatible with standard techniques for molecular and cellular analyses, including PCR, Western blotting and cryosectioning followed by immunofluorescence staining.